Wydatki na utrzymanie ratusza w Krakowie XVI–XVIII wieku - Szlęzak, Karolina (Roczniki Dziejów Społecznych i Gospodarczych, 2014)
Karolina Szlęzak Expenditure to maintain the town hall in Kraków from the 16th to 18th century (Summary) The excellently preserved town archives in Kraków, and above all, the sources of finance, enable extensive research to be conducted on the expenditure incurred to maintain Kraków’s town hall. The most important sources are the well preserved records regarding the city’s income and expenditure, which contain a lot of information about the expenses incurred for this purpose. In the 16th and 17th century, expenses to meet the needs of the town’s chancellery, to provide materials for the town hall building and to carry out maintenance works inside the building were noted in the section titled praetorii necessaria. Other expenses “regarding the town hall”, relating in particular to repair and construction works, are significantly dispersed in the accounts. The accounts show that throughout the period under discussion the town authorities employed permanent workers to perform some tasks within the town hall building and paid them weekly wages, while other tasks were performed by artisans and workers employed to complete specific tasks. The expenses that can be identified show that with the gradual impoverishment of the town, maintaining the town hall was an increasing burden on its budget. It could be said that the Kraków town hall building is a specific reflection of the state of the town’s finances. During the 16th century, the building prospered and was enlarged and enhanced, but fell into disrepair during Kraków’s political and economic slump.